A mountain of millipedes V: three new genera of Odontopygidae from the Udzungwa mountains, Tanzania (Diplopoda, Spirostreptida, Odontopygidae) - Enghoff, Henrik (European Journal of Taxonomy, 2016)
Three new genera of Odontopygidae are described, all based on new species from the Udzungwa mountains, Tanzania, and all monotypic: Casuariverpa gen. nov. (type species: C. scarpa gen. et sp. nov.), Yia gen. nov. (type species: Y. geminispina gen. et sp. nov.), and Utiliverpa gen. nov. (type species: U. decapsulatrix gen. et sp. nov.). Similarities and differences between the new genera and other genera are discussed.